FIQH OF TRAFFIC IN ACEH: AN OVERVIEW OF HUMAN SECURITY - Mumtazinur, Mumtazinur; Rispalman, Rispalman (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
There are 3 things that want to be explained further in this research, namely: how are traffic practices regulated in traffic fiqh in Aceh, and how are ideas and implementation of human security values through traffic fiqh in Aceh? Apart from that, this research also reviews the background to the birth of traffic fiqh for the Acehnese public. This research is qualitative with a descriptive analysis approach. The results found that driving practices regulated in traffic fiqh also strengthen what is regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation, but by using a religious approach to touch the public's awareness of the importance of protecting a sense of security for themselves and others.